Implementation of Persuasive Cued Click Points (PCCP) with the Integration of CAPTCHA and Sound Signature - Anjumol, PS; Amina Beevi, A (International Journal of Computer Sciences and Engineering, 2025)
Various graphical password schemes have been proposed as an alternative to text-based passwords. We propose and examine the usability and security of Persuasive Cued Click Points (PCCP) with a supportive sound signature, a cued-recall graphical password technique. Users click on one point per image for a sequence of images and they are asked to select a sound signature corresponding to each click-point. In PCCP, the next image will be based on the previous click-point. PCCP provides greater security than Pass Points because the number of images increases the workload for attackers. The cued-click point application in this project can be used to enter into a private SMS area, where the SMSs from specified numbers are kept hidden from the Inbox of the ANDROID mobile. As the solution to image gallery attacks digital watermarking is used in the images. In addition to these, we propose to implement a CAPTCHA which ensures the user to be a human and not any machine. Thus additional security to spambot can be ensured.